The Impact of Different Industrial Classification Schemes on Firm Performance: An IVs Analysis - Yong, S.L.; Ingham, H. (Center for Promoting Ideas (CPI), USA, 2012)
Market concentration ratio is argued to be an important driver of the firm performance. The measurement of its influence, however, is difficult since it is considered to be an endogenous variable. This paper applied the instrumental variables (IVs) approach using the SCP paradigm to model company performance. A panel analysis is carried out against a sample of 641 companies listed on the Main Board of Bursa Malaysia, over the period 2001 to 2006. The Durbin-Wu-Hausman (DWH) test results provide some support for the contention that the market concentration ratio variables are endogenous for SIC and Bursa classifications. After the market concentration ratio variables have been instrumented, it has a positive impact on firm performance. In addition, firm performance was found to be positively related to leverage, but negatively affected by firm capital intensity and openness.